Comparative genomics, infectivity and cytopathogenicity of Zika viruses produced by acutely and persistently infected human hematopoietic cell lines. - Bingjie Li; Hsiao-Mei Liao; Hebing Liu; Shien Tsai; Jing Zhang; Guo-Chiuan Hung; Pei-Ju Chin; Yamei Gao; Shyh-Ching Lo (PLoS ONE, 2018)
Zika virus (ZIKV), an arthropod-borne virus, has emerged as a major human pathogen. Prolonged or persistent ZIKV infection of human cells and tissues may serve as a reservoir for the virus and present serious challenges to the safety of public health. Human hematopoietic cell lines with different developmental properties revealed differences in susceptibility and outcomes to ZIKV infection. In three separate studies involving the prototypic MR 766 ZIKV strain and the human monocytic leukemia U937 cell line, ZIKV initially developed only a low-grade infection at a slow rate. After continuous culture for several months, persistently ZIKV-infected cell lines were observed with most, if not all, cells testing positive for ZIKV antigen. The infected cultures produced ZIKV RNA (v-RNA) and infectious ZIKVs persistently ("persistent ZIKVs") with distinct infectivity and pathogenicity when tested using various kinds of host cells. When the genomes of ZIKVs from the three persistently infected cell lines were compared with the genome of the prototypic MR 766 ZIKV strain, distinct sets of mutations specific to each cell line were found. Significantly, all three "persistent ZIKVs" were capable of infecting fresh U937 cells with high efficiency at rapid rates, resulting in the development of a new set of persistently ZIKV-infected U937 cell lines. The genomes of ZIKVs from the new set of persistently ZIKV-infected U937 cell lines were further analyzed for their different mutations. The 2nd generation of persistent ZIKVs continued to possess most of the distinct sets of mutations specific to the respective 1st generation of persistent ZIKVs. We anticipate that the study will contribute to the understanding of the fundamental biology of adaptive mutations and selection during viral persistence. The persistently ZIKV-infected human cell lines that we developed will also be useful to investigate critical molecular pathways of ZIKV persistence and to study drugs or countermeasures against ZIKV infections and transmission.